The influence of cataractus vision in the individual characteristics of handwriting and the implications in the work of forensic document examiner - Pertsinakis, Michail (Wydawnictwo Uniwersytetu Wrocławskiego, 2017)
The effects of cataractus vision on handwriting performance are evaluated. Six cata-ract patients were enrolled with an average age of 74.8 yrs and completed a specially designed questionnaire with samples of their signature pre-operatively and three-months post-operatively. The signatures were analyzed through a four-eye principle peer re-viewed examination focusing on six basic general characteristics of writing line quality, general design, size, arrangements, spacing and slant and their sub-elements. The quali-tative analysis showed that cataractus vision causes a decrease of line quality and differ-ences between the pre- and post- surgical samples on the sub-element of size. General design, intra-allograph ratio and slant were not influenced by the compromised vision.
Keywords: pismo odręczne; podpis; wizualna informacja zwrotna; cechy graficzne; katarakta; ekspert sądowy